2019
DOI: 10.1177/1945892419877554
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Rhinitis Is Associated With Loss of Energy and Concentration Difficulty: A Cross-sectional Study

Abstract: Objective To assess whether loss of energy and concentration difficulty are related to allergic rhinitis. Design A cross-sectional study. Setting Secondary care allergy outpatients. Participants A total of 100 patients with allergic rhinitis and 96 healthy subjects. Main Outcome Measure: Loss of energy and concentration difficulty were assessed through a survey using the Beck Depression Inventory-II (BDI-II). Results The average BDI-II score was higher in the allergic rhinitis population than in the healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…Our findings are in accord with previous studies that have demonstrated that the depression risk in AR patients is higher than patients without AR [ 14 , 39 , 40 ]. It has been shown that the severity of depression was associated to disease activity and was even more profound when atmospheric pollen is high in individuals with seasonal AR [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in accord with previous studies that have demonstrated that the depression risk in AR patients is higher than patients without AR [ 14 , 39 , 40 ]. It has been shown that the severity of depression was associated to disease activity and was even more profound when atmospheric pollen is high in individuals with seasonal AR [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…According to this survey, nasal congestion also left many of the participants feeling uncomfortable, frustrated, and having to slow down in the morning. Robles-Figueroa et al [ 16 ], in their cross-sectional study, reported a loss of energy and concentration difficulty more frequently in AR patients compared to healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of life in patients who suffer from sinonasal conditions is significant. This is highlighted in a manuscript by Robles-Figueroa et al 13 who demonstrated an independent association of allergic rhinitis with loss of energy and concentration difficulty. In addition, allergic rhinitis may also contribute to lingual tonsil hypertrophy as suggested by Coban et al 14 Yet, establishing a diagnosis of allergic rhinitis may be elusive.…”
mentioning
confidence: 91%
“…This is highlighted in a manuscript by Robles-Figueroa et al. 13 who demonstrated an independent association of allergic rhinitis with loss of energy and concentration difficulty. In addition, allergic rhinitis may also contribute to lingual tonsil hypertrophy as suggested by Coban et al.…”
mentioning
confidence: 91%